Homoeopathy and Exfoliative Dermatitis: An Evidence-Based Clinical Case Report of Exfoliative Dermatitis (Advancements in Homeopathic Research, 2025)
Exfoliative dermatitis, also known as Erythroderma,  is a severe and life-threatening condition that presents  with diffuse erythema & scaling of the skin. It is one  the uncommon skin disease conditions affecting  both males & females and almost all age groups.  Therapies like corticosteroids, anti-histamines &  immunosuppressant/immunomodulatory medications  are generally used to treat exfoliative dermatitis.  However, these therapies only give symptomatic  relief, not permanent disease improvement. In  homoeopathy, there is a lot of literature regarding  treating different skin diseases, such as exfoliative  dermatitis. This article illustrates a documented case  report of a patient with exfoliative dermatitis. In this  particular case, exfoliative dermatitis condition is  treated by Sulphur, based on the constitutional totality  of the patient. The improvement was documented  by proper treatment interpretation and photographic  evidence during follow-up.[1]
Keywords: Exfoliative dermatitis; Homoeopathy; Sulphur